Cost analysis of severe burn victims in Southwest China: A 7-year retrospective study - Zhuo Zeng; Ning Li; Ling Yang; Xue Feng; Fangqing Zuo; Gaoxing Luo; Yizhi Peng; Zhiqiang Yuan (Frontiers Media S.A., 2023)
BackgroundSevere burn injury can be a life-threatening experience and can also lead to financial issues for suffers. The purpose of the current study was to analyze the direct hospitalization costs of severe burn inpatients in Southwest China.MethodsData related to all inpatients admitted with severe burns [total body surface area (TBSA) ≥30%] pooled from 2015 to 2021 were reviewed retrospectively at the Institute of Burn Research of Army Medical University. Demographic parameters, medical economics, and clinical data were obtained from medical records.ResultsA total of 668 cases were identified. The average age was 37.49 ± 21.00 years, and 72.3% were men. The average TBSA was 51.35 ± 19.49%. The median length of stay of inpatients in the burn intensive care unit was 14 [interquartile range (IQR): 5.0-34.8] days, and the median length of stay (LOS) was 41 (IQR: 22.0-73.8) days. The mortality rate was 1.6%. The median total cost was 212,755.45 CNY (IQR: 83,908.80-551,621.57 CNY) per patient varying from 3,521.30 to 4,822,357.19 CNY. The direct cost of scald burns was dramatically lower compared with that of other types of burns, with 11,213.43 to 2,819,019.14 CNY. Medical consumables presented the largest portion of total costs, with a median cost of 65,942.64 CNY (IQR: 18,771.86-171,197.97 CNY). The crucial risk factors for medical cost in our study were TBSA, surgical frequency, LOS, depth of burn, and outcome.ConclusionWe conclude that an effective burn prevention program, shorter hospital stays, and facilitating the healing of wounds should be focused on with tailored precautionary protocols to reduce the medical costs of inpatients with severe burns.